Design and Implementation of an ETL-Process to Transfer Wound-Related Data into a Standardized Common Data Model - Przysucha, Mareike; Hüsers, Jens; Liberman, Daniil; Kersten, Oliver; Schlüter, Aphrodite; Fraas, Sebastian; Busch, Dorothee; Moelleken, Maurice; Erfurt-Berge, Cornelia; Dissemond, Joachim; Hübner, Ursula (German Medical Data Sciences 2023 – Science. Close to People., 2023)
For observational studies, which are relevant especially for chronic conditions like chronic wounds, the Observational Medical Outcomes Partnership (OMOP) Common Data Model (CDM) offers a standardized database schema. In this study an ETL process for the transition of wound related data was developed. After understanding the data in general and mapping the relevant codes to concepts available in OMOP, the ETL process was implemented. In a first step, a generic algorithm to convert data to a csv format was implemented in Java. The resulting csv file was then processed within KNIME to be loaded into an OMOP CDM conformant database. During the whole ETL process, HL7 FHIR CodeSystem and ConceptMap resources were used for coding and mapping. First clinical test cases to retrieve data were successfully processed as an example to demonstrate the feasibility and usefulness. They concerned wound size at the first visit and the main issues of patients in the wound quality of life questionnaire (n = 24). In general, the ETL process worked well, yet some challenges arose, like post coordinated SNOMED codes or conditions, which might occur more than once.
CRIS-Team Scopus Importer:2023-09-22
Keywords: ETL Process; OMOP CDM; Wound Care